Customers’ housing-switching behavior in Chongqing, China: A conceptual framework from the perspective of pull-push mooring theory - Yang, Hui Hui; Cui, Ruifu; Chong, Wei Ying (INTI International University, 2020)
A myriad of research has been carried out to explain customers’ buying intention and motivation. Taking a new approach this study has applied the pull-push mooring theory to explain buying intention in context of Chongqing China Real Estate market especially on customers’ housing-switching behavior. The purpose of this study is to examine the mediating role of perceived security risk on customers’ housing-switching behavior with a theoretical approach. It sets forth a conceptual framework that seeks to link systematically the push motivation, pull motivation, perceived security risk and switching intention.